اثر اسلوب القصة المبتورة في تحصيل تلاميذ الصف السادس الابتدائي في مادة التعبير التحريري (Journal Of Educational and Psychological Researches, 2015)
The current research aims to identify the impact of the amputated story style in the collection of sixth graders in elementary in the written expression subject.The researcher, intentionally, chose Al-Ameen primary hybrid school which belongs to the directorate of education in Baghdad / Karkh first.  The number of people of the sixth grade three classes. The researcher chose the two classes randomly to represent one of the experimental group, the number (32) pupils (male and female) have studied the expression subject by the amputated story style. Other control group, the number (32) pupils studied according to the traditional method.The researcher prepared the lesson plans and presented to the experts, the researcher chose eight texts presented to a group of experts to select five of them to represent the search tool, the researcher statistically processed her data by using the arithmetic mean, standard deviation, the bilateral test for two independent samples, and (Ka2 square).The most important findings of the research is the outweigh of  the pupils of the experimental group over the control group students in the written expression subject. The researcher concluded to the advantage of teaching by using the narrative texts when teaching the written expression subject by the amputated story style for students in sixth grade, because of its role to support the performance of expression when the students will balance the traditional manner, the researcher recommended a number of recommendations and suggestions.